Prehospital Intubation is Associated with Favorable Outcomes and Lower Mortality in ProTECT III. (3rd September 2017) - Denninghoff, Kurt R.; Nuño, Tomas; Pauls, Qi; Yeatts, Sharon D.; Silbergleit, Robert; Palesch, Yuko Y.; Merck, Lisa H.; Manley, Geoff T.; Wright, David W.
Abstract: Objective : Traumatic brain injury (TBI) causes more than 2.5 million emergency department visits, hospitalizations, or deaths annually. Prehospital endotracheal intubation has been associated with poor outcomes in patients with TBI in several retrospective observational studies. We evaluated the relationship between prehospital intubation, functional outcomes, and mortality using high quality data on clinical practice collected prospectively during a randomized multicenter clinical trial.Methods : ProTECT III was a multicenter randomized, double-blind, placebo-controlled trial of early administration of progesterone in 882 patients with acute moderate to severe nonpenetrating TBI. Patients were excluded if they had an index GCS of 3 and nonreactive pupils, those with withdrawal of life support on arrival, and if they had documented prolonged hypotension and/or hypoxia. Prehospital intubation was performed as per local clinical protocol in each participating EMS system. Models for favorable outcome and mortality included prehospital intubation, method of transport, index GCS, age, race, and ethnicity as independent variables. Significance was set at α = 0.05. Favorable outcome was defined by a stratified dichotomy of the GOS-E scores in which the definition of favorable outcome depended on the severity of the initial injury.Results : Favorable outcome was more frequent in the 349 subjects with prehospital intubation (57.3%) than in the other 533 patients (46.0%, p = 0.003). Mortality was also lower in the prehospital intubation group (13.8% v. 19.5%, p = 0.03). Logistic regression analysis of prehospital intubation and mortality, adjusted for index GCS, showed that odds of dying for those with prehospital intubation were 47% lower than for those that were not intubated (OR = 0.53, 95% CI = 0.36–0.78). 279 patients with prehospital intubation were transported by air. Modeling transport method and mortality, adjusted for index GCS, showed increased odds of dying in those transported by ground compared to those transported by air (OR = 2.10, 95% CI = 1.40–3.15). Decreased odds of dying trended among those with prehospital intubation adjusted for transport method, index GCS score at randomization, age, and race/ethnicity (OR = 0.70, 95% CI = 0.37–1.31).Conclusions : In this study that excluded moribund patients, prehospital intubation was performed primarily in patients transported by air. Prehospital intubation and air medical transport together were associated with favorable outcomes and lower mortality. Prehospital intubation was not associated with increased morbidity or mortality regardless of transport method or severity of injury.